Legal Protection Of PPAT Deeds After The Expansion Of The Regency Of Konawe District And South Konawe District - Raitno Raitno; Achmad Sulchan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The research objective to be achieved in this research is to explain the Legal Protection of Land Deed Making Officials (PPAT) based on Government Regulation Number 37 of 1998 concerning Land Deed Making Officials. This research uses empirical juridical research method.Based on the research, it is concluded that the Land Deed Making Official (PPAT) is a General Official who has the authority to make Transitional Deeds of Land, namely buying and selling, exchanging, grants, income into the company (inbreng, sharing of joint rights, granting Building Use Rights / Hak Pakai over Hak Milik land, granting Mortgage Rights, granting power to grant mortgages based on Article 2 paragraph (1) Government Regulation Number: 37 of 1998 concerning Land Deed Making Officials.